Combination of cuprizone and experimental autoimmune encephalomyelitis to study inflammatory brain lesion formation and progression. Issue 12 (24th August 2017) - Rüther, Bernhard Josef; Scheld, Miriam; Dreymueller, Daniela; Clarner, Tim; Kress, Eugenia; Brandenburg, Lars‐Ove; Swartenbroekx, Tine; Hoornaert, Chloé; Ponsaerts, Peter; Fallier‐Becker, Petra; Beyer, Cordian; Rohr, Sven Olaf; et al.
Abstract: Brain‐intrinsic degenerative cascades are a proposed factor driving inflammatory lesion formation in multiple sclerosis (MS) patients. We recently described a model combining noninflammatory cytodegeneration (via cuprizone) with the classic active experimental autoimmune encephalomyelitis (Cup/EAE model), which exhibits inflammatory forebrain lesions. Here, we describe the histopathological characteristics and progression of these Cup/EAE lesions. We show that inflammatory lesions develop at various topographical sites in the forebrain, including white matter tracts and cortical and subcortical grey matter areas. The lesions are characterized by focal demyelination, discontinuation of the perivascular glia limitans, focal axonal damage, and neutrophil granulocyte extravasation. Transgenic mice with enhanced green fluorescent protein‐expressing microglia and red fluorescent protein‐expressing monocytes reveal that both myeloid cell populations contribute to forebrain inflammatory infiltrates. EAE‐triggered inflammatory cerebellar lesions were augmented in mice pre‐intoxicated with cuprizone. Gene expression studies suggest roles of the chemokines Cxcl10, Ccl2, and Ccl3 in inflammatory lesion formation. Finally, follow‐up experiments in Cup/EAE mice with chronic disease revealed that forebrain, but not spinal cord, lesions undergo spontaneous reorganization and repair. This study underpins the significance of brain‐intrinsic degenerative cascades for immune cell recruitment and, in consequence, MS lesion formation. Main Points: Cuprizone‐induced cytodegeneration triggers monocyte, lymphocyte, and granulocyte recruitment into the forebrain. Peripheral immune cell recruitment induces acute axonal injury. Cytodegeneration augments cerebellar inflammation in experimental autoimmune encephalomyelitis.